TINDAK TUTUR EKSPRESIF DALAM FILM THE KISSING BOOTH KARYA VINCE MARCELLO (SUATU ANALISIS PRAGMATIK) - Talumingan, Mouren Theresia; Lasut, Theresia M.C; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Mouren Theresia Talumingan1Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Dra. Theresia M. C. Lasut, M.Hum2Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Donald Ringgo Lotulung, S.S, M.Hum3Â  Â  Â This study entitled â€œExpressive Act in the Film The Kissing Booth by Vince Marcello: A Pragmatic Analysisâ€. It is written to identify, classify and analyze the kinds and functions of Expressive Act in the Film The Kissing Booth. The method that is used in this research is descriptive method and the data of expressive act were taken from the film The Kissing Booth. The data have been analyzed by using theory of Searle (1976). There are six kinds of expressive act in the film The Kissing Booth by Vince Marcello, those are apologizing, praising, thanking, congratulating, greeting and blaming. The functions that have been found are expressive act expressing apologizing, expressive act expressing praising, expressive act expressing thanking, expressive act expressing congratulating, expressive act expressing greeting, and expressive act expressing blaming, while function like pardoning and condoling were not found in the film The Kissing Booth. It is expected that this study will help students and readers in learning pragmatics especially on expressive act found in the film._ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _Keywords: Expressive Act, Pragmatic, The Kissing Booth